Disaster by design the Aral Sea and its lessons for sustainability - Edelstein, Michael R.; Cerny, Astrid; Gadaev, Abror (Bingley, U.K. : Emerald, 2012)
Disaster by Design: The Aral Sea, Lessons for Sustainability addresses the impacts of the Aral Sea disaster. The virtual disappearance of what was the world's fourth largest inland body of water was neither natural nor accidental. It was the result of deliberate policy decisions. The sea's disappearance is hardly the entire disaster. Instead, we find an accumulation of cascading effects, beginning with the decision to grow cotton, reached remotely in Moscow, that altered the farming practices surrounding the Aral Sea. Unsustainable choices resulted in soil salinization, water pollution and toxic blowing sands, impacting the entire bioregion and beyond. A remote island was used to test biological weapons. Uzbekistan, most notably Karakalpakstan, was the autonomous republic at the epicenter of the disaster. Sustainable prospects exist, including renewable energy, permaculture and strengthening the social fabric amidst poverty and ecological collapse. This volume of Research in Social Problems and Public Policy is essential reading for everyone concerned with averting environmental disaster and instead creating livable, sustainable communities. Disaster by Design is a clarion call and an insightful study of Central Asia today.
Section one : the multiple disasters of the Aral Sea / Michael R. Edelstein -- An overview of the Aral Sea disaster / Abror Gadaev, Zikrilla Yasakov -- Going with the flow : economic impacts from the overuse of irrigation / Ilkhomjon Niyazov, Farhod Ahrorov, with Astrid Cerny, Michael R. Edelstein -- Pollution and salinization : compounding the Aral Sea disaster / Farhod Ahrorov, Olim Murtazaev, Bahtiyor Abdullaev -- Death and rebirth island : secrets in the U.S.S.R.'s culture of contamination / Michael R. Edelstein -- Potential climate and hydrological changes in the Aral Sea Region / James R. Miller, Imtiaz Rangwala, Debjani Ghatak -- The significance of being downstream : Uzbek concerns over the Rogun Dam / Murad Askarov -- Section two : the Aral disaster in historical perspective / Michael R. Edelstein -- A last movement for a lost sea / Yusup S. Kamalov -- Aral sea analogs in the American west / Howard Horowitz -- Disaster by design : the multiple caused catastrophes of the Aral Sea / Michael R. Edelstein -- Section three : cotton, cotton everywhere, but not a drop to drink : agriculture as the villain / Astrid Cerny, Michael R. Edelstein -- What went wrong : the case of un-ecological agriculture / Michael Wilson -- The nonarable Aral : loss of productivity in Uzbek agriculture / Farhod Ahrorov, Ilkhomjon Niyazov -- Cotton in our ears : water, agriculture, and climatic change in the post Aral context / Shavkat Hasanov ... [et al.] -- Water footprints : integrated water resource management to the rescue in the Aral Sea Basin / Inna Rudenko ... [et al.] -- Section four : adapting to catastrophe : cascading social impacts of the Aral Sea disaster / Michael R. Edelstein -- The tragedy of the Aral : counting on cotton, a region loses its people / Astrid Cerny -- Reflections on growing up in the Karakalpakstan Region / Aziz Murtazaev -- An unhealthy place to live : prioritizing public health and addressing environmental contamination in Karakalpakstan / Ramona Lall -- A physician's observations of Karakalpak health / Rakhmon U. Arzikulov, Laylo L. Almatova, Saodat Safarova -- Ecological change in the Aral Region : adaptations by the spoonbill and black-crowned night heron / Mukhtor Turaev -- Environmental change as a threat to the Khorezm heritage / Gavkhar Salaevna Durdieva -- Whose disaster is it anyway? : romancing the world heritage status in Uzbekistan / Flavia Alaya -- Section five : designing solutions : social, ecological and technological approaches / Michael R. Edelstein -- New thinking and new approaches : a bioregional response to the lost Aral Sea / Yusup S. Kamalov -- Renewable social energy : Mahalla / Lola Gulyamova -- Clearing the pipes : providing potable water through well restoration / Abror Gadaev, Gulmira Boboeva -- Renewing with renewables : direct solar energy use in developing countries / William J. Makofske -- Getting the salt out : innovative solar technologies for rural clean water / Eshkuvat Arzikulov, Qamariddin N. Srojev -- Renewable energy as a key factor for sustainable development in Uzbekistan / Ashraf Khodjaev -- Permaculture restoration of the Aral Sea watershed / Andrew Jones -- Section six : lessons of the Aral Sea disaster : implications for social learning / Michael R. Edelstein -- Aral Sea demise as a dry run for climate change : from cumulative to cascading impacts / Michael R. Edelstein -- Highlands-to-sea cooperation in the Aral Sea basin : linking or sinking? / Michael H. Glantz.
Keywords: Political Science -- General; Political Science -- Public Policy -- Environmental Policy; Nature -- Natural Disasters; Social impact of environmental issues; Natural disasters; Environmental disasters -- Aral Sea Watershed (Uzbekistan and Kazakhstan)